Implementation of Think Pair Share (TPS) Learning Strategies to Improve Students' Mathematical Communication Skills on Integer Materials in Class VII SMP Negeri 1 Tigabinanga 2014/2015 Academic Year - Esron Frananta Tarigan (Indonesian Journal of Education and Mathematical Science, 2022)
The type of research used in this research is classroom action research where action research is research that has the aim of improving the quality of learning in the classroom so that there are improvements in the classroom. The purpose of this study was to improve students' mathematical communication skills in learning integer material through Think Pair Share (TPS) learning strategies. The subjects of this study were class VII students of SMP Negeri 1 Tigabinanga for the academic year 2014/2015 Class VII-1 with a total of 38 students. In accordance with this type of research, this research has several stages which are cycles. Based on the results of the research presented in Chapter IV, conclusions can be drawn that learning by applying the Think Pair Share (TPS) strategy can improve students' mathematical communication skills seen from the increase in the average test results of students in cycle I and cycle II. The results of the student's mathematical communication ability test in the first cycle obtained an average score of 2.51 with a student's mathematical communication ability level of 60.52% or a low category. In the second cycle, the average score of the students' mathematical communication ability test reached 2.91 with the students' mathematical communication ability level of 84.21% or the medium category. This means that the Think Pair Share (TPS) learning strategy can improve students' mathematical communication skills, especially on integer material in class VII SMP Negeri 1 Tigabinanga academic year 2014/2015.